Molecular mechanisms underlying the role of the centriolar CEP164-TTBK2 complex in ciliopathies - Rosa E Silva, Ivan; Binó, Lucia; Johnson, Christopher M; Rutherford, Trevor J; Neuhaus, David; Andreeva, Antonina; Čajánek, Lukáš; van Breugel, Mark (Structure, 2022)
Cilia formation is essential for human life. One of the earliest events in the ciliogenesis program is the recruitment of tau-tubulin kinase 2 (TTBK2) by the centriole distal appendage component CEP164. Due to the lack of high-resolution structural information on this complex, it is unclear how it is affected in human ciliopathies such as nephronophthisis. Furthermore, it is poorly understood if binding to CEP164 influences TTBK2 activities. Here, we present a detailed biochemical, structural, and functional analysis of the CEP164-TTBK2 complex and demonstrate how it is compromised by two ciliopathic mutations in CEP164. Moreover, we also provide insights into how binding to CEP164 is coordinated with TTBK2 activities. Together, our data deepen our understanding of a crucial step in cilia formation and will inform future studies aimed at restoring CEP164 functionality in a debilitating human ciliopathy.
Keywords: mutace; Microtubule Proteins; mikrotubulární proteiny; Ciliopathies; stabilita proteinů; vazebná místa; HEK293 Cells; vazba proteinů; Protein Stability; proteinové domény; lidé; Protein Serine-Threonine Kinases; Mutation; Protein Binding; Protein Domains; HEK293 buňky; Models, Molecular; proteiny asociované s mikrotubuly; Protein Conformation; molekulární modely; Circular Dichroism; ciliopatie; konformace proteinů; cirkulární dichroismus; Microtubule-Associated Proteins; protein-serin-threoninkinasy; Binding Sites; Humans